2022
DOI: 10.3390/nu14081637
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics-Supplemented Low-Protein Diet for Microbiota Modulation in Patients with Advanced Chronic Kidney Disease (ProLowCKD): Results from a Placebo-Controlled Randomized Trial

Abstract: The probiotics-supplemented low-protein diet in chronic kidney disease (ProLowCKD) was a single-centre, double-blind, placebo-controlled, randomised trial that was conducted to investigate whether the association between a low protein diet (LPD) and a new formulation of probiotics (Bifidobacterium longum and Lactobacillus reuteri) was effective at reducing traditional uremic, microbiota-derived, and proatherogenic toxins in sixty patients affected by advanced CKD. After 2 months of a LPD—a reduction in blood u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In addition, it was found that L. reuteri combined with Clostridium butyricum retarded cisplatin‐mediated renal lesions by microbial reconstitution, increasing butyrate production and inhibiting renal inflammation (Hsiao et al, 2021). A clinical trial showed a formulation of probiotics, including B. longum and L. reuteri , was effective at decreasing host‐ and microbial‐derived toxins in patients with advanced CKD (De Mauri et al, 2022). B. animalis is an extensively reported probiotics, which has been found to improve human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that L. reuteri combined with Clostridium butyricum retarded cisplatin‐mediated renal lesions by microbial reconstitution, increasing butyrate production and inhibiting renal inflammation (Hsiao et al, 2021). A clinical trial showed a formulation of probiotics, including B. longum and L. reuteri , was effective at decreasing host‐ and microbial‐derived toxins in patients with advanced CKD (De Mauri et al, 2022). B. animalis is an extensively reported probiotics, which has been found to improve human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…These contradictory conclusions might be based on the bene cial or adverse effects of blautia of different species on human health [36][37][38].Bi dobacterium has been proved to be able to regulate the intestinal microecological balance, rebuild the integrity of intestinal barrier, and improve human immune function [39][40][41][42]. Although there was controversy about the usefulness of bi dobacterium alone in the treatment of CKD, previous studies have shown that bi dobacterium combined with traditional Chinese medicine could play a renal protective role in CKD by inhibiting the in ammatory reaction of macrophages in the kidney and intestine [43].In addition, the association of probiotics with low protein diet might play a bene cial role in the control and regulation of microbiota derived and atherogenic toxins in CKD patients [44].Prevotella was generally considered to be symbiotic bacteria because they were widespread in healthy people and rarely participated in infection. It was reported that only a few strains caused opportunistic endogenous infections, including chronic infections, abscesses and anaerobic pneumonia [45][46][47].Megamons was involved in the metabolism of carbohydrate fermentation to SCFA[48], so we assumed that megamons might antagonize CKD by affecting the diversity of SCFA.…”
Section: Discussionmentioning
confidence: 99%
“…The synbiotic capsules (GeriLact brand, Iran) supplementation containing a mix of probiotics and FOS as prebiotic might increase IS and parathyroid hormone levels in HD patients ( Mirzaeian et al, 2020 ). A low-protein diet plus a new formulation of probiotics ( Bifidobacterium longum and Lactobacillus reuteri ) was effective in reducing IS in patients affected by advanced CKD ( De Mauri et al, 2022 ). Synbiotic therapy, which consisted of a combination of high-molecular weight inulin, FOS, and galacto-oligosaccharides (GOSs) and the probiotic component including nine strains from the Lactobacillus , Bifidobacteria , and Streptococcus genera, decreased serum PCS of CKD patients with enrichment of Bifidobacterium and depletion of Ruminococcaceae after 6 weeks (4-week washout) in a randomized, double-blind, placebo-controlled, crossover trial ( Rossi et al, 2016 ).…”
Section: Clinical Trialmentioning
confidence: 99%